LEGENDA KBO IWA : ASAL-USUL DANAU BATUR DI BALI - Erlis Nur Mujiningsih (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2015)
Abstract: This paperstudies the Bali legend that is the former of Lake Batur. The background story of this legend is the story of Kbo Iwa. Based on the study f Olrix Epic Law, the story of Kbo Iwa is found in all laws except the fifth and sixth i.e. the opposing state law and the legal skeleton of twin brothers. Typically the name